Pemanfaatan TikTok sebagai Media Pemasaran Brand Fashion Arkline untuk Menarik Konsumen Gen Z - Erwin Permana; Najma Nury; Sabrina Oktavia; Risya Zahrotul Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Local fashion brands in Indonesia are increasingly favored by consumers due to their affordable prices and competitive quality compared to imported products. A key strategy for gaining market share is digital marketing, especially through TikTok. This study analyzes the sales growth strategy of Arkline, a local fashion brand that successfully utilizes TikTok for marketing. Using a descriptive qualitative approach, data were collected from official digital sources. The findings reveal that TikTok is highly effective in reaching Gen Z, who prefer visual and interactive content. Arkline's strategies include creating trend-based videos, engaging with audiences via TikTok Live, and collaborating with popular influencers. These efforts enhance brand awareness, strengthen audience engagement, and drive purchase decisions. The TikTok Shop feature also facilitates in-app purchases, leading to higher sales conversions. Overall, TikTok proves to be a powerful marketing tool for Arkline in building closer relationships with consumers, expanding market reach, and boosting competitiveness. With adaptive strategies aligned with digital trends, local brands can fully leverage TikTok’s potential in the evolving fashion industry.